2017
DOI: 10.1186/s13639-017-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic partial reconfigurable hardware architecture for principal component analysis on mobile and embedded devices

Abstract: With the advancement of mobile and embedded devices, many applications such as data mining have found their way into these devices. These devices consist of various design constraints including stringent area and power limitations, high speed-performance, reduced cost, and time-to-market requirements. Also, applications running on mobile devices are becoming more complex requiring significant processing power. Our previous analysis illustrated that FPGA-based dynamic reconfigurable systems are currently the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…This difference was further investigated, analyzed, and detailed in [21], [38]. From our previous work [20], [21], it was observed that the partial reconfiguration time overhead is in the range of milliseconds for the bit files of similar sizes. All these facts and our previous work [20], [21], [40], [49] illustrate that this difference between theoretical and experimental values for reconfiguration time overhead is quite normal.…”
Section: ) Analysis On Reconfiguration Time Overheadmentioning
confidence: 98%
See 3 more Smart Citations
“…This difference was further investigated, analyzed, and detailed in [21], [38]. From our previous work [20], [21], it was observed that the partial reconfiguration time overhead is in the range of milliseconds for the bit files of similar sizes. All these facts and our previous work [20], [21], [40], [49] illustrate that this difference between theoretical and experimental values for reconfiguration time overhead is quite normal.…”
Section: ) Analysis On Reconfiguration Time Overheadmentioning
confidence: 98%
“…From our previous work on dynamic and partial reconfigurable hardware architectures for data mining/analytics applications [20], [21], [40], [49] on embedded devices, it was observed that the percentage of reconfiguration time was amortized and decreased, as the computation complexity (i.e., the number of iterations/computations) increases as well as the size of the data increases; however, the percentage of reconfiguration time was significant for lower number of iterations/computations and smaller data sizes [20], [21]. Conversely, for our DRH designs for cryptographic algorithms, the percentage of reconfiguration time remains almost the same for each configuration.…”
Section: ) Analysis On Execution Times For Drhmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the reconfigurable circuitry is getting much attention recently in electronic industry, whether it is a digital application such as embedded system, data mining etc. [5,6] or it is an RF frontend application such as amplifier, antenna etc. [7,8].…”
Section: Introductionmentioning
confidence: 99%